Enhancing creative thinking, critical thinking, and interactional skills through problem-solving group projects among undergraduate English majors in Japan - Onoda, Sakae (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper discusses how group problem-solving projects can enhance learners’ creative and critical thinking skills while improving their interactional skills. According to the L2 literature, intensive use of such tasks can facilitate an optimal L2 learning environment that promotes a range of effective learning behaviours. Problem-solving tasks help learners achieve linguistic, affective, and social learning goals critical to L2 learning. This paper reports a mixedmethods study comparing the effects of such projects with those of teacher-led activities that maximised student interactions, both of which are deemed effective for L2 learning because they motivate language use. Participants consisted of two intact classes each with 24 third- and fourth-year English majors in a private university in Japan. Each task took up 50 minutes of a semi-content-based course. Results indicate that the projects significantly improved participants’ creative, critical, and L2 interactional skills compared with teacher-led activities. Participants’ feedback also revealed pedagogic benefits of group problem-solving projects of value to other educational settings.